Pemanfaatan Livelihood Assets Untuk Ketahanan Ekonomi Komunitas Rural di Sekitar Kawasan Penyangga Taman Nasional Zamrud - Yoskar Kadarisman; Nurhamlin Nurhamlin; Rina Susanti; Alika Nurmala Siregar (Indonesian Journal Publisher, 2025)
This community service activity is carried out with the aim of providing knowledge and understanding to the community about the use of livelihood assets to increase the economic resilience of rural communities around the buffer area of the Emerald National Park. People in this region mostly live from natural products, but do not fully understand how to optimally manage assets to support economic sustainability. Education and counselingwas provided to the people of the buffer zone in Sungai Apit District, Siak Regency. Implementation of activities is carried out using counseling methods, focus group discussions (FGD) and direct mentoring. The implementation team consists of three lecturers and is supported by local community leaders. The activity participants consisted of members of the local community who showed positive responses during implementation. This response can be seen from the enthusiasm of the participants in discussions, sharing experiences and direct practice regarding the use of assets in managing natural resources in buffer areas. Management of livelihood assets, such as human, natural, social, physical and financial assets, is carried out using the Asset-Based Community Development (ABCD) approach. The results of the community service show an increase in community knowledge, understanding and skills in managing natural resources sustainably, which contributes to improving economic welfare and the sustainability of the Zamrud National Park Buffer Zone. Knowledge increased by 23.4%. The community service activity process was published on the online media youtube https://www.youtube.com/watch?v=d6EtqNhVCVc and published on the online news media https://voxindonews.com/read/news/2024-10-06-tim-kjfd-sosiologi-unri-perkuat-kapasitas-masyarakat-Sekitar-taman-nasional-zamrud-siak.